Tasklets: enabling end user programming of web widgets. (1st January 2013) - Manjunath, Geetha; Murty, M. Narasimha; Sitaram, Dinkar
Mobile widgets are now popular and form a new paradigm of simplified web. Probably, the best experience of the web is when a user has a widget for every frequently executed task, and can execute it anytime, anywhere on any device. However, creating a widget today requires knowledge of programming, web technologies and protocols. In this paper, we propose a new method of web simplification that enables an end-user to create simple 'single-click' widgets for a personal task – without any programming. For this, we introduce a new concept called Tasklet to represent a user's personal interaction and model it using an instruction set over websites. These Tasklets can be programmed by demonstration and are executed using a Web Virtual Machine that virtualises changes to web pages. We believe our approach opens up a different perspective of WWW as not just 'web of pages' but 'web of tasks'.